THE EFFECT OF STRATEGIC LEARNING IN ENHANCING STRATEGIC FLEXIBILITY AN ANALYTICAL STUDY AT THE MINISTRY OF HEALTH CENTER - Dr. Tariq Kadhim Shlaka; Russell Khalaf Al-Zaidi (Scholar Express Journals, 2022)
The research dealt with the impact of strategic learning in its dimensions (knowledge perception, knowledge absorption, knowledge transfer) in achieving strategic flexibility with its dimensions (responsive flexibility, proactive flexibility), at the center of the Iraqi Ministry of Health. In improving its practice and adoption of these variables, and based on the importance of the urgent variables, the research adopted the descriptive analytical approach, and the research sample was intentional, which included (88) managers and their assistants and heads of departments in the Ministry’s center. Statistical programs (SPSS) to analyze the primary data, with the adoption of descriptive and inferential statistics methods (arithmetic mean, standard deviation, relative difference coefficient, relative importance, Pearson correlation coefficient, simple linear regression coefficient) to test the research hypotheses, and the results of the statistical analysis were concluded in the most prominent results That all the correlation and influence relationships were good and significant, which indicates the essential role that strategic learning plays. G in strengthening the strategic flexibility of the .Ministry of Health
Keywords: Strategic Learning; Strategic Flexibility; Ministry Of Health